DDRE-31. FEASIBILITY AND BIOLOGIC ACTIVITY OF A KETOGENIC / INTERMITTENT FASTING DIET IN GLIOMA PATIENTS. (25th March 2021) - Schreck, Karisa; Hsu, Fang-Chi; Berrington, Adam; Henry-Barron, Bobbie; Vizthum, Diane; Blair, Lindsay; Kossoff, Eric; Easter, Linda; Whitlow, Christopher; Cervenka, Mackenzie; Barker, Peter; Blakeley, Jaishri; et al.
Abstract: BACKGROUND: There has been increasing interest in exploring ketogenic diet therapies (KDT) in patients with glioma given the poor prognosis. The purpose of this single-arm, open label phase 2 study was to rigorously examine the feasibility, safety, systemic biological activity, and cerebral activity of a KDT in patients with glioma. METHODS: 25 patients with biopsy-confirmed WHO Grade 2–4 astrocytoma with stable disease following adjuvant chemotherapy were enrolled in an 8-week GLioma Atkins-based Diet (GLAD). GLAD consisted of 2 fasting days (calories<20% calculated estimated needs) interleaved between 5 modified Atkins diet days (net carbohydrates≤20 gm/day) each week. The primary outcome was dietary adherence by food records. Markers of systemic and cerebral activity included weekly urine ketones, serum insulin, glucose, hemoglobin A1c, IGF-1, and MR spectroscopy at baseline and week 8. RESULTS: 21 patients completed the study. 80% of patients reached ≥40 mg/dL urine acetoacetate during the study. 48% of patients were adherent by food record. The diet was well-tolerated with two grade 3 adverse events (neutropenia, seizure). Measures of systemic activity including hemoglobin A1c, insulin, and fat body mass decreased significantly, while lean body mass increased. MR spectroscopy demonstrated increased ketone concentrations (β-hydroxybutyrate (bHB) and acetone (Ace)) in both lesional and contralateral brain, compared to baseline. Higher total choline (tCho) and glutamine (Gln) levels were observed in lesional as compared to contralateral brain at baseline, and both decreased following intervention. Average ketonuria correlated with cerebral ketones in lesional (tumor) and contralateral brain (bHB Rs0.52, p=0.05). There were no differences in cerebral metabolites in IDH-mutant glioma after controlling for ketonuria. CONCLUSIONS: The GLAD dietary intervention, while demanding, produced meaningful ketonuria, and significant systemic and cerebral metabolic changes in participants. Participant ketonuria correlated with cerebral ketone concentration and appears to be a better indicator of systemic activity than patient-reported food records.